Characterization of Self-Knowledge in Adolescent’s Students for the Choice of Pedagogical Carrers (Global Journal of Human-Social Science, 2018)
Background The professional election in students has turned into a problem social educationally in resolute Cuba as of the present moment Objective To characterize self-knowledge in adolescents for the choice of pedagogical careers in students Methods The investigation covered a period from April 2017 to May 2018 A descriptive transactional design was used with a descriptive study under a sample of 40 eleventh grade students from the IPU Mariano Clemente Prado of the city of Santa Clara Cuba Preliminary instruments were used such as structured interviews with teacher guides and adolescent students Results Nevertheless the dedication to the study is a quality little recognized by the students Conclusions The pedagogical professional choice is not oriented in the sample under adequate student selfknowledge
Keywords: self-knowledge; professional choice; pedagogical careers; adolescents; didactic; educational process